Matching fertilization with available soil water storage to tackle the trade-offs between high yield and low N2O emissions in a semi-arid area: Mechanisms and solutions - Xiaorong Wu; Junjie Li; Xuanke Xue; Rui Wang; Wenhan Liu; Baoping Yang; Zhikuan Jia; Xudong Zhang; Qingfang Han (Agricultural Water Management, 2023)
Large fertilizer nitrogen (N) input has created favorable conditions for nitrous oxide (N2O) emissions in semi-arid areas. However, it remains to be determined whether the major contradictions between high yield and N2O emissions reduction can be reconciled by matching fertilization with water availability. A 3-year field experiment was conducted in the Loess Plateau of northwest China, monitored N2O fluxes over five N application rates (0, 120, 175, 230, and 285 kg N ha−1), and examined the environmental factors and crop production in a rainfed maize field. Results showed that available soil water storage at sowing (ASWS) is crucial in promoting soil N2O emissions by altering soil NO3--N, organic C, and organic N availability in semi-arid agroecosystems. The cumulative N2O emissions exponentially increased with increasing N rates. However, the cumulative N2O emissions were moderately low (1.20 kg N ha−1) at the N application rate of 230 kg ha−1, where maize yield was maximized, after which N2O emissions remarkably increased by 27.88 %. This result suggests that reduced N application to levels satisfying crop needs could significantly reduce N2O emissions with a minor yield penalty. Furthermore, water availability determines the absorption and utilization of nutrients by crops on the Loess Plateau and ultimately determines grain yield. Therefore, an N2O emission-yield curve was established to determine whether the target crop yield could be obtained by adjusting water availability and N fertilization rates while reducing N2O emissions. Our results suggest that N application rates at 218.7–230.0 kg ha−1, ensuring ASWS at 209.5–215.2 mm at sowing and precipitation within 61–90 days after sowing at 184.2–194.0 mm is ideal for matching fertilization with water availability to balancing high yield and mitigating N2O emissions in the study region.